Perception of consent among dental professionals - Shaila Tahir; Farkhanda Ghafoor; Shaheena Nusarat; Amanullah Khan (Journal of Medical Ethics and History of Medicine, 2009)
Background: Informed Consent concept has been recognized in all patient care fields. The contents and wordings of the informed consent are still being debated and experimented. Dental care services have considered the role of informed consent since 1980's, after some legal claims of malpractices.Methodology: A cross-sectional analytic study was undertaken involving 375 senior dental students and fresh graduates in their house job. A self-administered questionnaire explored their knowledge, attitude and practices regarding the need and importance of informed consent in dental services. The study instrument was designed keeping in view the content of courses in dental education and international standards. The questionnaire was pre-tested on a small group for assessing the suitability and validity of the responses. Results: The data was entered in SPSS version 16 and cross-tabulated through it. Most of the respondents (87%) were aware of the concept of informed consent, 6.9% considered it unnecessary and 21.9% were not practicing it. Invasiveness of dental procedure was found to be directly related to the need of including informed consent. Major justification for presence of informed consent was to protect the dentist from any legal proceedings.Conclusion: Dental professionals were aware about the informed consent as a step, but were unaware about its precise significance, content application and practice.